STRATEGI KONTEN KREATIF UNTUK MENINGKATKAN ENGAGEMENT UMKM DI SOCIAL MEDIA - Ardani, Shilvia Putri; Widiya Lestari Harahap (Puslitabmas Batam Tourism Polytecnic, 2024)
This research aims to investigate and analyze the impact of implementing creative content strategies in increasing the engagement level of Micro, Small and Medium Enterprises (MSMEs) on social media platforms. With increasing competition in the digital market, MSMEs need innovative approaches to build their online presence and maintain consumer engagement. The research results show that creative content strategies, such as the use of attractive visuals, effective storytelling, and a variety of multimedia content, have a positive impact on the level of user interaction. A significant increase was seen in the number of likes, shares and comments on MSME content after implementing this strategy. This research provides in-depth insight into the important role of creative content in MSME digital marketing strategies and contributes to a practical understanding of how to leverage social media to build stronger interactions with consumers.